Access to Health Insurance and Health Care for Hispanic Children in the United States. Issue 1 (July 2021) - Perreira, Krista M.; Allen, Chenoa D.; Oberlander, Jonathan
Health insurance gives families access to medical services and protects them against the costs of illness and medical treatment. Insured children are more likely than their uninsured peers to use medical services, preventive health services, have a usual source of care, and have fewer unmet medical needs. In this article, we review trends in health insurance coverage for Hispanic children and the factors that influence their coverage. We then discuss health care utilization among Hispanic children and barriers to health care utilization. We conclude with a discussion of strategies to improve Hispanic children's health care access in the age of COVID-19.